EDUKASI KREATIF DAN PEMBERDAYAAN POTENSI PERTANIAN - Kastowo, Chryssantus (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Community Service Program is a community service activity in certain areas which is carried out in groups. KKN 78 UAJY is oriented towards the type of KKN SOCIETY 5.0 which is carried out without any direct KKN activities in the specified area. The KKN Society 5.0 aims for students to be able to carry out KKN activities online. Group 2 got a location in Jepitu Village which is in Girisubo District, GunungKidul, Special Region of Yogyakarta. The work program that will be carried out by the group is the potential of the village and making digital textbooks. To collect existing data, the group collects data through the website. This potential work program for Jepitu Village is by processing the resources owned in this village such as the coastal area which is managed for tourism, then a guidebook is made to make processed from garden products such as peanuts into “peyek”. Another work program created by the group is making textbooks for elementary school children. The hope is that the work program created by the group can be useful for the community for the progress of the village.